2016
DOI: 10.21760/jaims.v1i4.6922
|View full text |Cite
|
Sign up to set email alerts
|

Review of Paneer and Cheese in context of Kilat and Kurchika

Abstract: Paneer and Cheese are being commonly used food item in India presently. It is a rich source of milk protein, calcium, Vitamin A, Phosphorous, vitamins, minerals and protein, which are required by the body in high proportions for healthy growth and development. Cheese is made by fermentation of curd. It is a rich source of milk protein, fat, calcium and riboflavin. Direct reference is not available in Ayurveda classics but it can be correlated with Kilat and Kurchika successively on the basis of their procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…Cheese has many types, and the composition of the cheeses varies according to its type. The most utilised cheddar cheese composition is 1.3% carbohydrates, 33.1% fat, 24.9% protein, and 36% water (Deshmukh and Vyas 2016). Almost a third of the world's milk is used in cheese manufacturing.…”
Section: Dairy Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheese has many types, and the composition of the cheeses varies according to its type. The most utilised cheddar cheese composition is 1.3% carbohydrates, 33.1% fat, 24.9% protein, and 36% water (Deshmukh and Vyas 2016). Almost a third of the world's milk is used in cheese manufacturing.…”
Section: Dairy Productsmentioning
confidence: 99%
“…The literature has shown that cheese contains more protein than milk or yoghurt. The percentage of protein in different milk or milk products is milk 3.3%, cheese 24.9%, and yoghurt 9% (Jost 2000;Lee and Lucey 2010;Deshmukh and Vyas 2016). The protein in milk or its products plays several crucial roles in maintaining good health and preventing several diseases.…”
Section: Reviewmentioning
confidence: 99%
“…Journal of Agriculture and Natural Resources (2021) 4(2): 284-294 ISSN: 2661-6270 (Print), ISSN: 2661-6289 (Online) DOI: https://doi.org/10.3126/janr.v4i2.33924 Paneer/Chhena Paneer which is also called Chhana or Chhena is a non-fermented cheese made from milkis fresh milk cheese, where the milk is coagulated with an acidic agent (like lemon juice, vinegar, or curd) (Deshmukh & Vyas, 2017). The whey is removed and the coagulated Paneer sets in some time.…”
Section: Creamsmentioning
confidence: 99%